Metabolic Changes in Zebrafish Larvae Infected with Mycobacterium marinum: A Widely Targeted Metabolomic Analysis - Chongyuan Sima; Qifan Zhang; Xiaoli Yu; Bo Yan; Shulin Zhang (Metabolites)
Objectives: To explore the metabolic changes in zebrafish larvae after infection with Mycobacterium marinum, this study adopted a widely targeted metabolomic approach to analyze the changes in the overall metabolic profiles of zebrafish larvae infected for 5 days. Methods: Data were collected by liquid chromatography–tandem mass spectrometry (LC-MS/MS). Mass spectrometry data were processed using Analyst 1.6.3 and MultiQuant 3.0.3 software, and multivariate statistical analysis was carried out. The KEGG database, HMDB database, and CHEBI database were used to screen and identify differential metabolites, and metabolic pathway enrichment analysis was performed through KEGG pathways. Results: A total of 329 metabolites were detected, among which 61 differential metabolites were screened. Specifically, 41 metabolites, such as kynurenine, isoallolithocholic acid, 2′-deoxyguanosine, indole-3-carboxaldehyde, and L-lactic acid, were downregulated, while 20 metabolites, such as L-palmitoylcarnitine, myristoyl-L-carnitine, dodecanoylcarnitine, 2-isopropyl-malic acid, and 2-methylsuccinic acid, were upregulated. KEGG metabolic pathway enrichment analysis indicated that these differential metabolites were mainly involved in metabolic pathways such as pyrimidine metabolism, nucleotide metabolism, the pentose phosphate pathway, and purine metabolism. Conclusions: This study demonstrated that significant changes occurred in multiple metabolites and metabolic pathways in zebrafish larvae after infection with M. marinum. The research results have improved the understanding of zebrafish as a model organism in the field of Mycobacterium research and laid a solid foundation for subsequent metabolomic-related research using zebrafish.